The effects of combination therapy with electroacupuncture and pelvic floor muscle exercise on stress urinary incontinence following radical prostatectomy: the protocol for a randomized controlled trial - Bi, Xiaoyun; Chen, Yuelai; Wu, Ruoyu; Gao, Weijia; Fan, Qian; Wang, Shengfei; Pan, Jiahua; Xue, Wei; Song, Qi-Xiang; Tang, Kangmin (Frontiers in Surgery, 2025)
BackgroundStress urinary incontinence (SUI) is one of the most common complications after radical prostatectomy (RP), affecting patients’ long-term quality of life. Electroacupuncture (EA) has been proven to be feasible in treating female SUI. However, considering the different pathogenesis of SUI between the two genders, it is essential to validate the efficacy of EA in male SUI after RP. So far, there has been no solid evidence confirming the benefit of EA in male SUI patients. Using the current study protocol, a prospective randomized controlled trial can be performed to reveal whether EA has additional benefits for accelerating SUI recovery after RP on the basis of pelvic floor muscle exercise (PFME). The outcomes from the proposed trial may provide key evidence for clinical guidance and practice to support the use of EA for post-RP SUI.MethodsIn this prospective, randomized controlled trial, patients with SUI symptoms 6 weeks after RP will be recruited and randomly assigned to either treatment group (PFME plus EA) or control group (PFME plus placebo EA). Standard sacroiliac and abdominal acupoints will be selected for EA treatment. For placebo EA, blunt-tipped needles will be used to stab the skin surface at the same acupoints. Daily PFME is conducted with a unified protocol in both groups. The primary outcome is defined as the change from baseline in the 1-h pad test weight at week 6. The efficiency will be assessed using the intention-to-treat analysis by a statistician blinded to the interventions.DiscussionThe study will provide a high level of evidence to justify the future application of EA by offering an alternative approach for the treatment of SUI after radical prostatectomy. Clinical Trial registrationClinicalTrials.gov, identifier NCT05773716.